Hubungan Motivasi dengan Perilaku Ibu Nifas dalam Perawatan Payudara - Erna Isnandira; Maria Ulfa (Journal of Ners and Midwifery, 2014)
Improper breast care will cause swelling on the breast and cracking on theÂ  nipples which make the process of breastfeeding difficult. When there is cracking on the nipples, breastfeeding process should be suspended until it is healed. Method: The research design was a correlational research using cross sectional approach. The research sample was 14 people at BPM Eny Kustyaningsih Kepanjen Kidul District of Blitar at Augus 03th until 14th, 2012, it was chosen using purposive sampling. The data was collected by observation using questionnaire. The data was analyzed using Spearman rank, with a significant level of â‰¤ 0.05. Result : The motivation of breast care in postpartum mothers was in category of enough at about 71.4%, 64.3% in behavior, with the Spearman Rank P-value of 0.008. Discussion : It should be held further education for the mothers, especially when the mother was in a pregnancy, so that new mothers had the attention, memory, imagination and highly motivated so that the motivation and behavior of breast care would be better.